An Overview Benefits and Risk of Smart Healthcare Application Using Internet of Things (International Journal of Innovative Research in Computer Science & Technology, 2021)
An Internet of Things (IoT) enables  devices to gather and share data directly with one another  and along with clouds, enabling for faster and more  effective data collecting, recording, as well as analysis.  This opens up a world of possibilities in a range of  industries, including such autonomous cars that recognize  wear and tear as well as schedule repairs, or trains that  dynamically calculate and broadcast anticipated arrival  times to waiting passengers. Nowhere is the Internet of  Things more promising than in health, in which its  concepts are already being applied to improve access to  treatment, improve quality, as well as, most importantly,  reduce costs. The use of different technologies, such as  information technology (IT), to complement and improve  current healthcare services has been the subject of much  study. The Internet of Things (IoT) has indeed been  widely utilized to connect current medical resources as  well as provide reliable, effective, and intelligent  treatment to the aged and chronically ill. Recognizing the  benefits and drawbacks of any innovation is critical to its  successful implementation. This article presents a  descriptive assessment of the Smart Healthcare Platform's  benefits and drawbacks. The smart healthcare platform's  history is also discussed.
Keywords: Healthcare Benefits; Healthcare; IOT; Smart Service; Smart Healthcare